Penerapan Data Mining Untuk Prediksi Layanan Produk Indihome Menggunakan Metode K-Nearst Neighbor - Arwa Ulayya Haspriyanti; Putri Taqwa Prasetyaningrum (Journal of Information System and Artificial Intelligence, 2021)
ABSTRACTPT. Telkom is a company engaged in the field of telecommunication that develops IndiHome product. IndiHome itself is the combination of product and service types including telecommunication, information, media and edutainment becomes one consisting internet service, internet voicete and interactive internet (UseeTV cable) or Triple Play. The development of a maximum marketing strategy requires an effective and efficient marketing mix. In principle, the marketing strategy provides direction in relation with variables such as market segmentation, target, positioning, and marketing mix element. In order to support this study, the variable used is operational variable for external and internal analysis. In this study, the method used is qualitative research method. Meanwhile, the type of the study is descriptive.The primary data is directly obtained from the research subject through observation, interview, and documentation. As seen from the large number of customer request related to the service product based on sales data for the past 1 year, it is important to get the sales prediction of best-selling service product, in order to facilitate the company in developing service provision planning. Furthermore, the use of data mining classification technique and K-Nearest Neighbor algorithm is needed to find out the best-selling service product sales. The result of this study is the prediction of the best-selling service product sales which is 1 from the total of 3 product types that are sold includingInternet, Internet Voice, and Internet Voice Useetv. It is based on the accuracy value towards the classification of the best-selling product sales of 99.99%.